Financial literacy and numerical ability: keys to better mortgage outcomes - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
The US mortgage crisis and its dire after effects have highlighted the criticality of financial literacy. And while most people would have picked up fundamental mathematical principles in schools, not everyone appreciates how arithmetic translates within the complex world of finance. Yet, given what has transpired with the subprime crisis, is it important for borrowers to appreciate complicated financial concepts before taking up a loan? A study of the US mortgage market, presented at a SMU School of Economics Seminar Series, provides some clues as it uncovers links between basic numerical skills and financial fate.